Experimental Metaphysics (Bloomsbury Academic, 2021)
Metaphysics, almost entirely neglected by experimental philosophers, is the central focus of Experimental Metaphysics. The volume brings together a range of views aimed at addressing the question of how cognitive science might be relevant to metaphysics.